Insights into the structure and reactivity of the catalytic site of nitrous oxide reductase - Carreira, Cíntia Catarina Sousa (2018)
Substantial part of the emissions of nitrous oxide (N2O), a powerful greenhouse gas, to the atmosphere comes from the incomplete denitrification in bacteria. N2O can only be detoxified by nitrous oxide reductase (N2OR), which catalyzes the last step of this pathway. This enzyme contains two distinct centers per monomer: CuA, the electron transfer center and “CuZ”, a tetranuclear copper-sulfide center, which can exists in two forms CuZ(4Cu2S) and CuZ*(4Cu1S). Most of the studies on the denitrification pathway have used soil denitrifying bacteria as models, while marine bacteria are understudied. This thesis presents an analysis of denitrification pathway of Marinobacter hydrocarbonoclasticus a marine bacterium capable of respiring nitrate under oxygen-limiting conditions. Here, the effect of pH (6.5, 7.5 and 8.5) on the denitrification pathway of this organism, as well as on the N2OR isolated from each of those growths, was investigated. These enzymes were characterized through biochemical, spectroscopic and structural studies. The expression profile of genes encoding the enzymes and accessory proteins involved in denitrification was analyzed, together with quantification of the by-products, nitrate and nitrite. These results showed lower levels of nirS expression at pH 6.5, which correlates with the accumulation of nitrite detected. In parallel, whole-cells reduction rates of NO and N2O demonstrated that denitrification is impaired at more acidic conditions, as the whole-cells are not able to reduce external N2O when grown at pH 6.5. The N2OR isolated from each growth exhibits differences at the “CuZ center”. At acidic growth conditions, N2OR has “CuZ center” mainly as CuZ*(4Cu1S), whereas when isolated from growths at 7.5 and 8.5, it is mainly as CuZ(4Cu2S). This was supported by spectroscopic data, sulfide quantification, and inspection of “CuZ center” X-ray structure, demonstrating the presence of an additional sulfur atom in the CuZ(4Cu2S) form. The effect of exogenous ligands on both forms of the “CuZ center” was re-visited and clarified. Direct electrochemistry of N2OR is reported for the first time, with the two signals observed, assigned to CuA and CuZ(4Cu2S) centers, with reduction potentials being in line with the ones determined by potentiometry (272 ± 10 mV and 65 ± 10 mV vs SHE at pH 7.6, respectively). This form of N2OR has lower specific activity (0.004 ± 0.001 U/mg) in the presence of physiological electron donor, cytochrome c552, compared to a N2OR with CuZ*(4Cu1S) (1.25 ± 0.07 U/mg). Fully reduced CuZ*(4Cu1S) is catalytically competent and in the presence of a stoichiometric amount of N2O originates CuZº intermediate. CuZº species can be reduced through intramolecular electron transference (IET) from CuA center, in a reaction 104 faster than IET in the CuZ*(4Cu1S). In the absence of substrate or electrons a novel “CuZ center” intermediate species is formed with a maximum absorption band at 617 nm, and having a [1Cu2+-3Cu1+] oxidation state. These studies shed new lights on the catalytic cycle, which was reassessed and discussed here.